2021
DOI: 10.51253/pafmj.v71i5.6326
|View full text |Cite
|
Sign up to set email alerts
|

Histological Consequences of Consumption of Energy Drink on Renal Tubules

Abstract: Objective: To investigate the outcomes of energy drink on renal tubules of albino rats. Study Design: Laboratory-based experimental study. Place and Duration of Study: King Edward Medical University, Lahore from Aug 2018 to Dec 2019. Methodology: Group A and B were experimental groups received 1.5ml/kg and 2.2ml/kg body weight of energy drink, respectively. Group C received 1ml/kg body weight of distilled water. Comparison among groups was made by applying One-Way ANOVA for quantitative varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Rasheed and colleagues [ 124 ] investigated the effects of energy drinks on renal tubules using albino rats as an experimental animal model. Their research showed histopathological changes in renal tubular cells, such as increased tubular vacuolisation, in rats exposed to energy drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Rasheed and colleagues [ 124 ] investigated the effects of energy drinks on renal tubules using albino rats as an experimental animal model. Their research showed histopathological changes in renal tubular cells, such as increased tubular vacuolisation, in rats exposed to energy drinks.…”
Section: Discussionmentioning
confidence: 99%